ANALISIS KELENGKAPAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) BERDASARKAN INDEKS GLOBAL REPORTING INITIATIVE (GRI) PADA BANK UMUM SYARIAH (BUS) DI INDONESIA - MUHAMMADINAH MUHAMMADINAH (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2016)
The purpose of this study was to determine the completeness of the disclosure of CSR (Corporate Social Responsibility) based index GRI (Global Reporting Initiative) in the Banking Companies Listed in Indonesia Stock Exchange and to know the completeness of the disclosure of CSR (Corporate Social Responsibility) based index GRI (Global Reporting Initiative ) on Islamic Banks (BUS) in Indonesia. As for the object of this study are all Islamic Banks in Indonesia. The research method used deskriptive analysis with content analysis is to identify the CSR practices in the banking industry using the Global Reporting Initiative (GRI) index. GRI CSR based on Islamic Banks in Indonesia is not yet complete, it is due to the existence of some items that are unlikely to be met by the banking industry, especially Islamic banking. It is expected the need for disclosure of items of financial statements in accordance with the operational activities of Islamic banking industry so that each indicator can be evaluated properly.Keywords: Disclosure of CSR, GRI Index